Photocatalytic Degradation of Synthesized Colorant Stains on Cotton Fabric Coated with Nano TiO2 (Journal of Fiber Bioengineering and Informatics, 2018)
Optimization of cured cotton textiles through self-cleaning property constructs the main goal ofpresent investigation. Cotton textiles with 0.1, 0.3, 0.5, 1 and 1.5 wt% were cured by Nano-titanium dioxide(P25 Degussa) with and without using cross-link method. Stability of the TiO_2 coatings is a particularrequirement for textiles because they are subject to frequent washing hence use of a suitable coatingcondition is necessary. During this study sucsinic acid was used as spacers to attach TiO_2 to cotton.Viscosity degree of titania particles to cotton fabrics is studied by burning method by determining thepercentage of titania coated. Further, following experiments were conducted: thermal behaviour of curingsamples with TGA, self-cleaning degree of curing cotton fabrics and stained samples with Dark green BNgreen 6 and Reactive orange V-2G dyes under irradiation of 20 & 400 W UV lamps using reflectancespectrophotometer, structure and morphology of titania coated cotton fabric through scanning electronmicroscopy (SEM) and crystallinity of titania coatings by X-ray diffraction (XRD). Tearing strength ofcured cotton fabrics was investigated before and after employing irradiation process. Results show thatstability of Nano TiO_2 coating and degree of self-cleaning cured with cross-link method is extremely higherthan in non cross-link operation and cotton cellulosic chains are not decomposed by photocatalytic activityof titania.
Keywords: Self-cleaning; titania; photocatalytic; cotton; cross-linking; irradiation